Time trial exertion traits of cycling's Grand Tours - Earnest, C. P.; Foster, C.; Hoyos, J.; Muniesa, C. A.; Santalla, A.; Lucia, A. (International Journal of Sports Medicine, 2009)
We examined 26 professional riders during time trial (TT) competitions of the Grand Tours of cycling (Tour de France and Vuelta Espana; 1997-2003) for the exertional characteristics of contending vs. non-contending (i.e., support) riders. We categorized HR time during TT into training impulse (TRIMP) defined from seasonal VO2max testing [Phase I (<ventilatory threshold (VT˜64% VO2max); Phase II (VT - respiratory compensation threshold, ˜83% VO2max); Phase III >RCP]. Races were: Short TT (<15 km; 8.9±2.9 km); Individual TT (>15 km; 48.12±8.7 km); Uphill TT (20.0±8.7 km) and Team TT (44.1±20.9 km). We observed statistically significant event-by-contender interactions for all TT (all, P<0.0001) except the short TT. During uphill TT, contenders exerted fewer total TRIMP (P<0.01), more Zone 3 TRIMP (P<0.05), and fewer Zone 2 TRIMP (P<0.01) vs. non-contenders. For individual TT, contenders accumulated more Total and Zone 3 TRIMP vs. non-contenders (all, P<0.05). Interestingly, during the team TT, contenders accumulated more Zone 3, and fewer Zone 2 TRIMP (all, P<0.05), despite having the opportunity to draft behind other riders while in paceline race formation. During TT events, contending riders compete at a level of exertion corresponding to a higher metabolic demand during the uphill TT, individual TT and team TT.